2019
DOI: 10.4102/phcfm.v11i1.1963
|View full text |Cite
|
Sign up to set email alerts
|

Professional nurses’ experiences of caring for patients in public health clinics in Ekurhuleni, South Africa

Abstract: Background Caring for patients is the core aspect of nursing and a cornerstone of all nursing duties. Although caring is seen as a critical component of nursing delivery and an essential characteristic of nursing, there seems to be a gap between theory and practice. Aim The aim of this article was to explore and describe the experiences of caring for patients by professional nurses in public health clinics in Ekurhuleni. Setting The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
(22 reference statements)
2
19
0
Order By: Relevance
“…Various studies on experiences of professional nurses in PHC clinical settings were also conducted in different parts of the world, and findings similar to a research study conducted by Nesengani 7 were reported. In a research study entitled ‘Primary health care: The experiences of nurses’ conducted in Chile, Garcίa-Vera et al 8 reported that even though the professional nurses were grateful of their work, they had negative experiences.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Various studies on experiences of professional nurses in PHC clinical settings were also conducted in different parts of the world, and findings similar to a research study conducted by Nesengani 7 were reported. In a research study entitled ‘Primary health care: The experiences of nurses’ conducted in Chile, Garcίa-Vera et al 8 reported that even though the professional nurses were grateful of their work, they had negative experiences.…”
Section: Introductionsupporting
confidence: 66%
“…2 To ensure caring in nursing, the caring actions should help patients feel better, whilst the absence of caring would affect patients psychologically, emotionally and physically. 2 , 3 In South Africa, clinics have become the cornerstone of the public health system. In this regard, it is necessary and expected that clinics provide comprehensive and integrated basic health programmes, with members of the public being treated with care, respect and compassion by all healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations